2021
DOI: 10.3390/ijerph18063094
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Health Anxiety for Hospital Staff Working during the Covid-19 Pandemic

Abstract: Background: During the COVID-19 pandemic, the likelihood that hospital staff will report symptoms of depression, anxiety, and stress has increased. The aim of this study was to evaluate the relative influences of circumstantial, demographic, and trait–state anxiety variables on health anxiety in this group. Methods: A total of 168 hospital staff members (mean age: 28.91 years; 56.5% females) participated in the study. They completed a series of questionnaires covering sociodemographic characteristics, health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
(43 reference statements)
1
13
1
1
Order By: Relevance
“…However, the result shows that they experienced high levels of anxiety. Further,anxiety levels are significantly higher among females (Alwani et al, 2020), female nurses in particular (Leodoro & Santos, 2020;Shayganfard et al, 2021). Moreover, biopsychological characteristics as women are greater vulnerable within the face of stressful events (Hosseinzadeh-Shanjani et al, 2020),which contrasts with the findings of previous studies showing that gender turned into no longer statistically significant (Shayganfard et al, 2021;Wilczyńska et al, 2019), opposite findings have also been reported.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…However, the result shows that they experienced high levels of anxiety. Further,anxiety levels are significantly higher among females (Alwani et al, 2020), female nurses in particular (Leodoro & Santos, 2020;Shayganfard et al, 2021). Moreover, biopsychological characteristics as women are greater vulnerable within the face of stressful events (Hosseinzadeh-Shanjani et al, 2020),which contrasts with the findings of previous studies showing that gender turned into no longer statistically significant (Shayganfard et al, 2021;Wilczyńska et al, 2019), opposite findings have also been reported.…”
Section: Resultscontrasting
confidence: 56%
“…During the Covid-19 pandemic, health workers felt depressed and worried so that anxiety increased in carrying out their duties due to the availability of personal protective equipment (Zhang et al, 2020).Previous studies have reported that the psychological disorders experienced by health workers during the Covid-19 pandemic were mostly caused by fear of transmission and infection in family, friends, colleagues, and the presence of negative stigma from the community (Handayani et al, 2020). Besides, being close to people infected with COVID-19 was related to anxiety (Marashi et al, 2020;Shayganfard et al, 2021) (Shayganfard et al, 2021). This can lead increase in the risk of mentalemotional problems.…”
Section: Introductionmentioning
confidence: 99%
“…Last, COVID-19-related restrictions not only negatively impacted health anxiety and its related fear of getting affected by the COVID-19 among hospital staff [ 4 , 15 ]; such conditions had an unfavorable impact also on the behavioral level to avoid postponing or canceling routine medical checks. To illustrate, among pregnant women and young mothers, higher health anxiety was associated with delaying or canceling routine health assessments [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this population all participants were in in-patient care and receiving therapy, thus the possibility of relapse was very low. When looking at other research being done in the area of psychosocial distress in the context of COVID-19, studies can be found on university students (Villani et al, 2021), health care workers (Shayganfard et al, 2021) and the general population (Wang et al, 2020). Further indicating that a change in people already diagnosed with major depression has not been investigated and may, for the afore-mentioned reasons, not be particularly likely.…”
Section: Discussionmentioning
confidence: 99%